OPTIMIZATION OF DIAGNOSTICS AND TREATMENT OF DIABETIC FOOT - Narzullaev Sh.Sh.; Saydullaev Z.Ya. (Research Focus International Scientific Journal, 2023)
This article is devoted to one of the main problems not only of surgery and endocrinology, but also of modern medicine - “diabetic foot” syndrome. Despite the development of medicine and diagnostic methods, timely diagnosis and complex treatment of various complications of diabetes mellitus remains a big problem.